Urgensi Perumusan Visi, Misi, Tujuan dan Sasaran Organisasi Islam - Samsidar; Syamsurianto; A. M. Nur Atma Amir; Sudirman; Rika Dwi Ayu Parmitasari (TAFAQQUH, 2023)
Over the years, management strategies have been used as a tool to transform and revitalize organizations, both public and non-profit. The main goal is to respond to possible upcoming environmental changes. Formulating a vision, mission, goals, and objectives is part of this management strategy. This article tries to reveal the importance of the relationship between these management strategy components in Islamic organizations. As an Islamic institution, it is very important to build an awareness system that is oriented towards sharia goals. This research is a qualitative research method using a library research approach. The results of this research indicate that Islamic organizations are a representation of efforts to achieve certain goals, namely Islam. Achieving this goal can only be achieved through implementing the vision, mission, goals, and targets of the Islamic organization itself, which are based on Islamic law.